Sexual Health Education Metode GAVIS Mencegah Kekerasan Seksual pada Anak Usia Sekolah - Latifah Susilowati; Dwi Yati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Violence against children is still a problem faced by the government. As much as 67% of the violence occurred in school-age children. The purpose of this study was to determine the effect of sexual health education with the GAVIS method as an effort to prevent sexual violence. In this study, children aged 9-12 years in the intervention group were given sexual health education using the GAVIS method, while the control group received lectures on sexual health and prevention of sexual violence. Data about children's attitudes were collected through filling out a questionnaire, then analyzed using a paired sample t-test. The results of the analysis showed the value of p = 0.003. Furthermore, it was concluded that the sexual health education intervention in the form of the GAVIS method had an effect on the attitudes of school-age children about the prevention of sexual violence.Keywords: sexual violence; school age children; GAVIS method; sexual health education; attitude ABSTRAK Kekerasan pada anak masih menjadi masalah yang dihadapi oleh pemerintah. Sebesar 67% kekerasan anak tersebut terjadi pada anak usia sekolah. Tujuan penelitian ini adalah mengetahui pengaruh sexual health education dengan metode GAVIS sebagai upaya pencegahan kekerasan seksual. Dalam penelitian ini anak usia 9-12 tahun pada kelompok intervensi diberikan sexual health education dengan metode GAVIS, sedangkan kelompok kontrol mendapatkan ceramah tentang kesehatan seksual dan pencegahan kekerasan seksual. Data tentang sikap anak dikumpulkan melalui pengisian kuesioner, lalu dianalisis menggunakan paired sample t-test. Hasil analisis menunjukkan nilai p = 0,003. Selanjutnya disimpulkan bahwa intervensi sexual health education berupa metode GAVIS berpengarh terhadap sikap anak usia sekolah tentang pencegahan kekerasan seksual.Kata kunci: kekerasan seksual; anak usia sekolah; metode GAVIS; sexual health education; sikap